EXPRESSIONS THAT CARE: A GUIDE TO CARE THROUGH ART IN ONCOLOGY - Cavalcanti Gomes, Andy; Luiz Henrique Coelho de Siqueira Teixeira; Eliane Nóbrega Albuquerque (Cadernos ESP, 2026)
Objective: To present the process of developing a psychological intervention proposal, with a focus on psychoeducation, through discussion groups and the use of artistic resources, designed for patients and their caregivers in an oncology ward at a referral general hospital. Method: The intervention guide was developed by psychology students, based on hospital psychology practice, and structured according to the Maguerez Arc. Observation of the reality revealed a scarcity of spaces for emotional expression and the strengthening of bonds in the context of oncology hospitalization, guiding the development of the material. Results: The activity promotes symbolic expression, the exchange of experiences, and a broader perception of the support network, contributing to the strengthening of bonds and the reduction of feelings of isolation. Final considerations: The proposal constitutes a powerful strategy for the humanization of care and can be applied by healthcare professionals in the hospital setting.
Keywords: Humanization of Assistance; Oncology; Mental Health; Medical Psychology; Psycho-Oncology